C 1s Peak of Adventitious Carbon Aligns to the Vacuum Level: Dire Consequences for Material's Bonding Assignment by Photoelectron Spectroscopy - Greczynski, Grzegorz; Hultman, Lars (Chemphyschem, 2017)
The C 1s signal from ubiquitous carbon contamination on samples forming during air exposure, so called adventitious carbon (AdC) layers, is the most common binding energy (BE) reference in X‐ray photoelectron spectroscopy studies. We demonstrate here, by using a series of transition‐metal nitride films with different AdC coverage, that the BE of the C 1s peak EBF varies by as much as 1.44 eV. This is a factor of 10 more than the typical resolvable difference between two chemical states of the same element, which makes BE referencing against the C 1s peak highly unreliable. Surprisingly, we find that C 1s shifts correlate to changes in sample work function ϕSA , such that the sum EBF+ϕSA is constant at 289.50±0.15 eV, irrespective of materials system and air exposure time, indicating vacuum level alignment. This discovery allows for significantly better accuracy of chemical state determination than offered by the conventional methods. Our findings are not specific to nitrides and likely apply to all systems in which charge transfer at the AdC/substrate interface is negligible. Zeros matter: The C 1s signal from adventitious carbon (AdC) is the most common binding energy (BE) reference in X‐ray photoelectron spectroscopy. It is shown here that the BE of the C 1s peak EBF is substrate dependent, which makes BE referencing highly unreliable. Surprisingly, C 1s shifts correlate to changes in the sample work function ϕSA , such that the sum EBF+ϕSA is constant irrespective of the materials system and air exposure time, indicating vacuum level alignment. This discovery allows for significantly better accuracy of chemical state determination.